Omega-3 Fatty Acids and Vitamin D Combination Affected TG Levels in Rattusnorvegicus with Limited Fat Intake - Adnyana, I Gede Angga; Aji Kresnapati, I Nyoman Bagus; Agus saputra, I Putu Bayu; Diarti, Maruni Wiwin; Jiwintarum, Yunan (Poltekkes Kemenkes Palu, 2023)
Vitamin D is a group of secosteroids that have fat-soluble properties. Vitamin D regulates calcium absorption, bone growth and remodeling, and regulates metabolic processes and immunity. Omega-3 fatty acids are a type of polyunsaturated fatty acids (PUFAs) that are essential fatty acids for humans. Omega-3 fatty acids have various positive effects on health, especially cardiovascular-related ones. This study aims to determine the effect of omega-3 fatty acid and vitamin D combination on the TG/HDL-C ratio in high fat fed Rattus norvegicus. The research design is experimental study with a post-test-only control group design. This study used 24 male rats aged 3–4 months with a body weight of 250–300 grams which were divided into four groups; negative control group, positive control group; treatment group one; and treatment group two. The high-fat diet (HFD) is an additional (emulsion) feed added to standard feed with increased fat composition. The results showed that increased triglyceride (TG) levels of 83.40 mg/dL and HDL levels of 62.60 mg/dL after consumed high-fat diet. There was a significant decrease in TG levels of 54.15 mg/dL (p=0.026) and a decrease in HDL of 53.00 mg/dL (p>0.05, α=0,05) after administration of Omega-3 and Vitamin D combination. Conclusions in this study is the intake Omega-3 and Vitamin D combination has a positive effect on TG levels. Still, this positive effect must be accompanied by limiting the fat intake to the body. Meanwhile, combining Omega-3 and Vitamin D did not significantly affect HDL levels.